2022
DOI: 10.4315/jfp-22-077
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus plantarum and Deoxynivalenol Detoxification: A Concise Review

Abstract: Mycotoxins are toxic secondary fungal metabolites that contaminate feeds, and their levels remain stable during feed processing. The economic impact of mycotoxins on animal production is mainly due to losses related to direct effects on animal health and trade losses related to grain rejection. Deoxynivalenol (DON) is a trichothecene mycotoxin with a worldwide prevalence of about 80%, which induces many toxic effects on human and animal health. Detoxification strategies to decrease DON levels in food and feed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 124 publications
0
3
0
Order By: Relevance
“…mixture on broiler chickens challenged with DON and Clostridium perfringens (CP), as previous research has suggested that Lactobacillus spp. strains may mitigate the negative effects of single challenge with mycotoxins or CP in the intestine [ 5 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…mixture on broiler chickens challenged with DON and Clostridium perfringens (CP), as previous research has suggested that Lactobacillus spp. strains may mitigate the negative effects of single challenge with mycotoxins or CP in the intestine [ 5 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lactobacillus spp. strains, in different forms—be it live cells, heat-inactivated cells, or culture supernatants—have demonstrated protective effects in chickens individually challenged with either DON or CP [ 5 , 24 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the detoxification of mycotoxins such as aflatoxins produced by A. flavus , various approaches have been reported to inactivate mycotoxins, including biological, chemical and physical methods. The biocontrol-based mycotoxin detoxification is widely recognized as specific, efficient, environment-friendly and sustainable methods; for example, mycotoxin removal by probiotics, cell-binding of mycotoxins, biodegradation, microbial consortia and recombinant enzyme analysis ( Kim and Chan, 2014 ; El-Baky and Amara, 2021 ; Liu et al., 2022 ; Maidana et al., 2022 ; Zadravec et al., 2022 ). On the other hand, information on detailed mechanisms of mycotoxin degradation by biocontrol approach is currently scarce ( Zadravec et al., 2022 ), for which LC-MS/MS or GC-MS/MS methods may help to elucidate the pathway of mycotoxin biodegradation ( Agriopoulou et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…With increasing energy costs, controlling temperature and humidity for contaminated low-value feed is economically questionable. Therefore, treatment with lactic acid or with lactic acid bacteria is increasingly propagated to prevent further fungal growth and mycotoxin production, numerous reviews exist on this topic (Dalié et al, 2010;Pawlowska et al, 2012;Oliveira et al, 2014;Hassan et al, 2016;Sadiq et al, 2019;Maidana et al, 2022;Smaoui et al, 2022). Interestingly, DON already present in the harvested material can also be reduced by lactic acid bacteria.…”
Section: Introductionmentioning
confidence: 99%